Going menopostal : what you (and your doctor) need to know about the real science of menopause and perimenopause - Alkon, Amy (BenBella Books, Inc., 2025)
"For women affected by conditions such as perimenopause and menopause, Going Menopostal empowers all women with the science and strategies they need to get the evidence-based care they expect and deserve"--